K(+ )channel openers restore verapamil-inhibited lung fluid resolution and transepithelial ion transport - Han, Dong-Yun (BioMed Central, 2010)
BACKGROUND: Lung epithelial Na(+ )channels (ENaC) are regulated by cell Ca(2+ )signal, which may contribute to calcium antagonist-induced noncardiogenic lung edema. Although K(+ )channel modulators regulate ENaC activity in normal lungs, the therapeutical relevance and the underlying mechanisms have not been completely explored. We hypothesized that K(+ )channel openers may restore calcium channel blocker-inhibited alveolar fluid clearance (AFC) by up-regulating both apical and basolateral ion transport. METHODS: Verapamil-induced depression of heterologously expressed human αβγ ENaC in Xenopus oocytes, apical and basolateral ion transport in monolayers of human lung epithelial cells (H441), and in vivo alveolar fluid clearance were measured, respectively, using the two-electrode voltage clamp, Ussing chamber, and BSA protein assays. Ca(2+ )signal in H441 cells was analyzed using Fluo 4AM. RESULTS: The rate of in vivo AFC was reduced significantly (40.6 ± 6.3% of control, P < 0.05, n = 12) in mice intratracheally administrated verapamil. K(Ca3.1 )(1-EBIO) and K(ATP )(minoxidil) channel openers significantly recovered AFC. In addition to short-circuit current (Isc) in intact H441 monolayers, both apical and basolateral Isc levels were reduced by verapamil in permeabilized monolayers. Moreover, verapamil significantly altered Ca(2+ )signal evoked by ionomycin in H441 cells. Depletion of cytosolic Ca(2+ )in αβγ ENaC-expressing oocytes completely abolished verapamil-induced inhibition. Intriguingly, K(V )(pyrithione-Na), K (Ca3.1 )(1-EBIO), and K(ATP )(minoxidil) channel openers almost completely restored the verapamil-induced decrease in Isc levels by diversely up-regulating apical and basolateral Na(+ )and K(+ )transport pathways. CONCLUSIONS: Our observations demonstrate that K(+ )channel openers are capable of rescuing reduced vectorial Na(+ )transport across lung epithelial cells with impaired Ca(2+ )signal.